The Trouble with “Gender”: A few critical Comments on the Italian “DDL Zan” - Monceri, Flavia (Soft Power, 2024)
On October 15th, 2013 the Italian Legislative Decree of August 14th, 2013, n. 93, passed, with amendments, into law (n. 119/2013), after a period in which the “urgency” to elaborate a law against “gender violence” had become gradually a public concern, supported also by relevant initiatives. In the media and the public opinion this law is called “feminicide law”, but the word feminicide is not to be found either in the title or the text. Rather, the headline of the law reads as follows: “Urgent provisions on security and to contrast gender violence, as well as on civil protection and compulsory administration of the provinces”. At that time my idea was, and still is, that this law be just another instance of misunderstanding gender, if the notion means directly “women” without further discussion, as I will try to very briefly show (Monceri, 2013).